Factors Affecting the Performance of Zakat Administration in Malaysia: An AHP Approach - Aznan Hasan; Muhamad Abduh; Rusni Hassan; Engku Rabiah Adawiah Engku Ali; Engku Muhammad Tajuddin Engku Ali; Nazrul Hazizi Noordin (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2021)
The primary objective of this study is to investigate the views of zakat professionals on the factors affecting the performance of zakat administration in Malaysia. This study started with library research to critically review previous literature on zakat administration, followed by the analytical hierarchy process (AHP). This study finds that the provisions of zakat law and collection mechanism are viewed as the most critical factors influencing the performance of zakat collection and distribution mechanism and public perception are viewed as the two main factors affecting the performance of zakat distribution administration in Malaysia. This study hopes to shed some light on how to improve the administration of zakat collection and distribution, especially the importance of having a standardized legislation and regulatory frameworks for zakat administration to be applied in all states in Malaysia.